1963
DOI: 10.1007/bf02654746
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cyclopropenoid fatty acid derivatives with hydrogen halides

Abstract: The treatment of Sterculia foetida oil with concentrated aqueous HC1 or with HBr in acetic acid results in the addition of one hydrohalogen molecule per cyclopropenoid moiety. Iodine value (I.V.) and infrared absorption measurements indicate that the mechanism parallels that of the polymerization of sterculic acid and involves the formation of four isomeric monounsaturated monohalo moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The following reactions were thought to occur with the products obtained depending upon the severity of the method used for the decomposition (100). Iodine values and infrared absorption measurements indicated to other workers (8) that the reaction of cyclopropenoid fatty acids with hydrogen halides involved the formation of four isomeric monounsaturated monohalo moieties as shown. The mechanism Nunn (196) suggested that sterculic acid polymerized by the addition of the carboxyl group across the double bond.…”
Section: Oxidationsupporting
confidence: 53%
“…The following reactions were thought to occur with the products obtained depending upon the severity of the method used for the decomposition (100). Iodine values and infrared absorption measurements indicated to other workers (8) that the reaction of cyclopropenoid fatty acids with hydrogen halides involved the formation of four isomeric monounsaturated monohalo moieties as shown. The mechanism Nunn (196) suggested that sterculic acid polymerized by the addition of the carboxyl group across the double bond.…”
Section: Oxidationsupporting
confidence: 53%
“…The present report deals with an analytical method based upon the measurement of the absorptivity at 11.05 microns after treatment with aqueous hydrochloric acid. The development of the absorption maximum at 11.05 microns is attributable entirely to the unsymmetrically disubstituted olefinic group CH2 || -CH2-C-CHCl-, resulting from the opening of the cycloprcpene ring (1).…”
Section: Infrared Absorption Methodsmentioning
confidence: 96%
“…The hydrochlorination of the cyclopropenoid moiety results in four isomers, only two of which have an absorption band at 11.05 microns (1). The proportion of the products responsible for the absorption maximum at this wavelength is, however, always the same.…”
Section: Infrared Absorption Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent hydrogenation reactions of this alcohol using Pd and Pt catalysts revealed that the cyclopropene ring was kept intact during reduction [20]. Halogenation reactions of CPEFA with concentrated aqueous hydrogen halides in acetic acid for 1 h gave isomeric mono-unsaturated monohalo compounds [21] (Eq. 3).…”
Section: Introductionmentioning
confidence: 99%